The Accidental Bioethicist - McCULLOUGH, Laurence B. (Cambridge quarterly of healthcare ethics, 2002)
Albert Jonsen in The Birth of Bioethics notes that his career in bioethics began with a phone call to him from soon-to-be colleagues at the University of California at San Francisco Medical Center. Bioethics didn't begin with a bang but as an accident in the root sense—something that happened, not by necessity, but rather by chance. Indeed, the opening chapters of Jonsen's book chronicle a series of accidents that helped to create the field of bioethics. Principal among these was the fact that physicians and biomedical scientists who became puzzled about the moral dimensions of their work and began to think about these puzzles sought help in doing so from moral theologians and philosophers. These physicians and scientists, for the most part, were university people. They thought broadly, not just deeply, about their work, but they just as well could have defined themselves by their academic discipline and departments and not reached beyond these familiar and comfortable intellectual confines to the “culture” of the humanities disciplines and departments. The theologians and philosophers whom these physicians and scientists sought out were also university people who also happened to have generous views of the intellectual life in their disciplines—atypical of the time, especially in philosophy. If C. P. Snow had been altogether right and if ungenerous self-understanding of their work by physicians, scientists, philosophers, and theologians had prevailed, bioethics might not have happened at all.